Sagot :
Answer: B
Step-by-step explanation:
Solution
Factoring the numerator and denominator to get;
⟹ (x + 1) (x + 4) (x + 5)/(x + 1) (x – 1)
Now cancel the common terms.
⟹ (x + 4) (x + 5)/(x – 1)
Example 2
Simplify (x2 – 4) / (x2+ 4x + 4)
Solution
Factor both the numerator and denominator to get.
⟹ (x + 2) (x – 2) / (x + 2) (x + 2)
Now cancel out common factors in the numerator and denominator to get.
= (x – 2) / (x + 2)
Example 3
Simplify the rational expression x / (x2 – 4x)
Solution
Factor x out in the denominator to get;
⟹x /x (x – 4)
On cancelling the common terms in the top and bottom, we get;
= 1 / (x – 4)
Example 4
Simplify the rational expression (5x + 20) / (7x + 28)
Solution
Factor out the GCF in both the numerator and denominator;
= (5x + 20) / (7x + 28) ⟹ 5(x + 4) / 7(x + 4)
On cancelling common terms, we get;
= 5/7
Example 5
Simplify the rational expression (x2 + 7x + 10) / (x2 – 4)
Hope it helps ! :)